Part-period Egg Production and Egg Quality Characteristics of Two Ecotypes of Nigerian Local Chickens and Their F1 Crosses - Momoh, O.M.; Ani, A.O.; Ugwuowo, L.C. (International Journal of Poultry Science, 2010)
Adaptation of the local chickens in Nigeria to the different agro-ecological zones has produced ecotypes that can be conveniently classified on the basis of body weight and size into two viz; Heavy Ecotype (HE) and Light Ecotype (LE). These distinct types may differ in their egg production characteristics. Short-term egg production and egg quality characteristics of HE and LE and their F1 crosses (HExLE and LExHE) were studied. The objective of the study was to evaluate the short-term egg production and quality traits of the HE, LE and their F1 reciprocal crosses. Data on percent hen-day production, egg number per hen, egg weight and egg mass of 50 pullets each of HE, LE, HEXLE and LEXHE were collected. Also, external and internal egg quality traits were assessed on a total of 640 eggs. Data were subjected to ANOVA technique. Result showed that there was no significant (p>0.05) genetic group effect on short-term percent hen-day production, egg number and egg mass. However, genetic group significantly affected egg weight (p